Role of interleukin-1 receptor 1/MyD88 signalling in the development and progression of pulmonary hypertension. Issue 2 (13th July 2016) - Parpaleix, Aurélien; Amsellem, Valérie; Houssaini, Amal; Abid, Shariq; Breau, Marielle; Marcos, Elisabeth; Sawaki, Daigo; Delcroix, Marion; Quarck, Rozenn; Maillard, Aurélie; Couillin, Isabelle; Ryffel, Bernhard; et al.
Pulmonary artery smooth muscle cell (PA-SMC) proliferation and inflammation are key components of pulmonary arterial hypertension (PAH). Interleukin (IL)-1β binds to IL-1 receptor (R)1, thereby recruiting the molecular adaptor myeloid differentiation primary response protein 88 (MyD88) (involved in IL-1R1 and Toll-like receptor signal transduction) and inducing IL-1, IL-6 and tumour necrosis factor-α synthesis through nuclear factor-κB activation. We investigated the IL-1R1/MyD88 pathway in the pathogenesis of pulmonary hypertension. Marked IL-1R1 and MyD88 expression with predominant PA-SMC immunostaining was found in lungs from patients with idiopathic PAH, mice with hypoxia-induced pulmonary hypertension and SM22-5-HTT + mice. Elevations in lung IL-1β, IL-1R1, MyD88 and IL-6 preceded pulmonary hypertension in hypoxic mice. IL-1R1 −/−, MyD88 −/− and control mice given the IL-1R1 antagonist anakinra were protected similarly against hypoxic pulmonary hypertension and perivascular macrophage recruitment. Anakinra reversed pulmonary hypertension partially in SM22-5-HTT + mice and markedly in monocrotaline-treated rats. IL-1β-mediated stimulation of mouse PA-SMC growth was abolished by anakinra and absent in IL-1R1 −/− and MyD88 −/− mice. Gene deletion confined to the myeloid lineage (M.lys-Cre MyD88 fl/fl mice) decreased pulmonary hypertension severity versus controls, suggesting IL-1β-mediated effects on PA-SMCs and macrophages. The growth-promoting effect of media conditioned by M1 or M2 macrophages from M.lys-Cre MyD88 fl/fl mice was attenuated. Pulmonary vessel remodelling and inflammation during pulmonary hypertension require IL-1R1/MyD88 signalling. Targeting the IL-1β/IL-1R1 pathway may hold promise for treating human PAH. The IL-1R1/MyD88 pathway is a treatment target for pulmonary arterial hypertension http://ow.ly/1Fpe3008RLs